Stakeholders Mapping on the Sustainability of Halal Tourism Development in Sabang City - Armanda, Dicky; D.A, Dyah Kuntorini; Zahara, Ana; Nurmasyahyati; Kurniawan, Rudi (Global Writing Academica Researching and Publishing, 2024)
This paper's subjects were the availability and viability of Sabang's halal sites and routes. We create a five-point framework for tourist stakeholders that explains how they can use their positions and teamwork benefits to manage destinations through regulation, conservation, and livelihood. We achieve this by referring to the underlying ideas and practices of sustainability as well as how stakeholder participation and involvement are included in the growth of sustainable tourism. The suggested pathways for halal tourism begin in Sabang, the city's center. The study employed qualitative techniques like field observations, focus groups, and interviews. Additionally, the geographical relationships between tourist attractions were identified, located, and plotted using GIS technology. The study's findings confirm Sabang's abundance of potential tourism resources for halal tourism development. Natural resources and Islamic heritage make up the majority of these resources. After the available tourism resources were identified, numerous potential halal tourism routes were suggested. Proposals for how tourism stakeholders can advance sustainable tourism will be included in the findings. As a result, determining a destination's tourism potential should begin with an inventory of its actual and potential tourism resources.